ANALYSIS OF SALTED FISH PROCESSING BUSINESS IN HAJORAN VILLAGE, CENTRAL TAPANULI REGENCY, NORTH SUMATERA - Sarumpaet, Lusi Erdiani; Yulinda, Eni; Anugerah, Tirta; Siburian, Juliana P; Nisari, Tika (Asian Journal of Aquatic Sciences, 2025)
The salted fish processing industry was one of the small and medium-sized business sectors that played an important role in supporting the economy of coastal communities. Salted fish products not only have a relatively high economic value, but also increase the durability of marine catches through traditional preservation processes. However, amidst fairly broad market opportunities, salted fish processing business actors often faced various challenges, especially regarding production cost efficiency, raw material price transmission, and income instability. This study analysed production costs, revenues, and profits from salted fish processing. The method used in this study was the survey method. Based on the results of the research that had been conducted, it was found that the average cost incurred by salted fish entrepreneurs was IDR 47,702,088 per month, with revenues of IDR 56,612,500 per month. The average profit was approximately IDR 8,910,412 per month